Current status of haematopoietic autologous stem cell transplantation in lymphoid malignancies: a European perspective. (26th May 2014) - Hübel, Kai; de la Rubia, Javier; Azar, Nabih; Corradini, Paolo
Abstract The use of autologous haematopoietic stem cell transplantation (ASCT) has increased considerably in lymphoid malignancies in the last decade, and it is now considered as the standard of care in particular circumstances. This review aims to present an overview of the current situation with ASCT in lymphoid malignancies in Europe, in terms of both current use and issues. It will also look briefly at ASCT in rarer haematological malignancies and at the future. It is intended as a reflection of opinion from selected centres in Europe and as an aid to understanding for those who are new to the area. The review is based on a series of four preceptorship meetings held in Europe in 2013.